Plant–soil feedback and plant invasion: effect of soil conditioning on native and invasive Prosopis species using the plant functional trait approach - Ali, Hamada E.; Al-Wahaibi, Ahmed M.; Shahid, Muhammad Shafiq (Frontiers in Plant Science, 2024)
Introduction Invasive species have been identified as a major threat to native biodiversity and ecosystem functioning worldwide due to their superiority in spread and growth. Such superiority is explained by the invasional meltdown phenomena, which suggests that invasive species facilitate the establishment of more invasive species rather than native species by modifying the plant-soil feedback (PSF). Methods We conducted a two-phase plant-soil feedback experiment using the native Prosopis cineraria and the invasive Prosopis juliflora in Oman. Firstly, we conditioned the soil by planting seedlings of native species, invasive species, native and invasive species “mixed”, and unconditioned soil served as a control. Secondly, we tested the feedback of these four conditioned soil on the two species separately by measuring the productivity (total biomass) and the performance in the form of plant functional traits (plant height, specific leaf area (SLA), leaf nitrogen content (Nmass), leaf carbon content (Cmass) and specific root length (SRL) of native and invasive species as well as the nutrient availability in soil (soil organic carbon (SOC) and soil total nitrogen (STN)). Results and discussion We found that the native species produced more biomass, best performance, and higher SOC and STN when grown in soil conditioned by native species, additionally, it gave lower biomass, reduced performance, and lower SOC and STN when grown in the soil conditioned by invasive and mixed species. These results suggest negative PSF for native species and positive PSF for invasive species in the soil conditioned by invasive species, which can be considered as red flag concerning the restoration of P. cineraria as an important native species in Oman, as such positive PSF of the invasive species P. juliflora will inhibit the regeneration of P. cineraria.